Pengembangan Desa Wisata Gerabah dalam Meningkatkan Pendapatan Masyarakat Pundong Bantul - Iputu Hardani Hesti Duari (Media Wisata, 2017)
Development of the tourism village aims at increasing the social well-being and educating the people in the field of development at the tourism sector, for the purpose is long-term in the next five years on 2021 that Indonesia could bring 10 million foreign tourists with the bases of development of tourist with special interest, one of them is travelled in tourism village. Pesona Indonesia program is designed by the ministry of tourism and creative economy is a program that is designed to encourage the progress and well-being of local society for multi-effect from the development of tourism itself in a recreational area that enables to expand the labour and the business of fields of tourism. It means that how can a program capable of blends of internal elements of socio-cultural-dynamic to the development with developing the sectors. In quantity and quality, the benefits and their impact can be looked at. The success of the village when developing its source has a strategic significance for improvements of socioeconomic for people and regions, thus welfare and continuation of tourism village of pottery can work in accordance with the development that is explorative and not exploitive. Especially when we consider in strategic locations tourist village of pottery is located in one the tourism in Parangtritis coast very phenomenal. The form of the final objective as a special target is growing the interest and the awareness for the village community especially around tourist village of pottery in sub-district Pudong , to develop this tourist village to be a productive village that able to provide the multiplier effect for increasing of income for the surrounding community by the presence of an increasing the employment opportunities, employment sector is as supporting indicator of and it is for support in the development of creative economy community base on local empowerment. The qualitative method is to determine the way to find, collect, cultivate and analyze and understand the social interaction by means of a deep interview so it will find a clear pattern as an approach which is the most effective to accelerate the development that refers to the basis of the basic of rights life for the community